Pelatihan kader Posyandu dalam upaya peningkatan kunjungan Posyandu Bougenville, Kelurahan Lok Bahu, Samarinda - Zahra, Nurul Fitriani Az; Azzahra, Rania Nasywa; Abdullah, Ahmad Fadhlil Azhim; Titania; Natasya, Adinda Naia; Maulany, Ahmad Daffi; Hardani, Iqbal Marcello Putra; Saputro, Alfonsus Dwi; Safariana, Nadia Sinta Aulia; Sari, Mila Warma; Rohmah, Nur; Permana, Lies; Agustini, Rina Tri; Nurrachmawati, Annisa (Jurnal Pengabdian Masyarakat: Humanity and Medicine, 2025)
Posyandu Bougainville in RT 46 Lok Bahu Village, Samarinda, faces challenges in increasing community participation, especially mothers of toddlers, in health activities. Lack of public awareness and appreciation of Posyandu cadres is a major problem. This research aims to increase visits to Posyandu through training cadres in creating digital promotional media and making souvenir products. The results of the training show an increase in cadres' skills in creating attractive promotional media as well as their ability to make souvenir products. After implementing the use of digital promotional media and giving souvenirs at posyandu activities, it showed that there was a significant increase in the number of visits to posyandu, from 20 in October to 26 in November. This training was not only successful in improving cadre skills, but also attracted community interest in participating in Posyandu activities.